MACHINE LEARNING UNTUK ANALISA POLA TREN PASAR DAN REDIKSI PERMINTAAN PRODUK MENGGUNAKAN METODE REGRESI LINEAR - Lisdarti, Lisdarti; -, yusril (JURNAL AKADEMIKA, 2024)
This research discusses the application of machine learning methods to analyze market trend patterns and predict demand for a product using the market sampling method. The case study raised in this research focuses on processing data from e-commerce platforms to identify factors that influence purchasing decisions and predict stock needs based on sales trend analysis. The main objective of this research is to develop a prediction system that can help e-commerce companies plan product marketing strategies and inventory management more effectively. The research results show that the use of machine learning, especially the market sampling method, is able to provide accurate and reliable predictions for decision making in the marketing business of a product that is trending on the market.